2022
DOI: 10.1155/2022/5915670
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Single‐Person Laparoscopic Appendectomy Using a Novel Brace‐Assisted Camera Holding System and Conventional Laparoscopic Appendectomy: A Neural Network Algorithm Analysis

Abstract: Background. Acute appendicitis represents one of the main causes of surgical emergencies. It can be approached as an open appendectomy or a laparoscopic appendectomy (LA). However, LA generally requires the cooperation of a surgeon and an assistant. This study aims to compare the safety and efficacy of the novel brace-assisted single-person laparoscopic appendectomy (BASPLA) with conventional laparoscopic appendectomy (CLA) in the treatment of patients diagnosed with acute appendicitis by neural network algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Especially in emergency surgery, it can achieve satisfactory clinical efficacy without requiring an assistant. 14 Wu, S et al, 2022 showed SILA performed with only conventional laparoscopic instruments was associated with reduced hospital stay and cost and higher cosmetic satisfaction in comparison to CLA. However, it is technically demanding and may increase operative time.…”
Section: Resultsmentioning
confidence: 99%
“…Especially in emergency surgery, it can achieve satisfactory clinical efficacy without requiring an assistant. 14 Wu, S et al, 2022 showed SILA performed with only conventional laparoscopic instruments was associated with reduced hospital stay and cost and higher cosmetic satisfaction in comparison to CLA. However, it is technically demanding and may increase operative time.…”
Section: Resultsmentioning
confidence: 99%
“…ASA is a condition in which the lesion has invaded the entire appendiceal wall, with marked swelling of the appendix and elevation of the outer appendiceal plasma membrane. 12 Due to the small size of the appendix in early childhood, the appendix wall is weak, with little basal tissue, and when circulatory disorders of appendiceal blood flow occur, the appendix is locally ischemic and necrotic, which is conducive to the propagation and growth of pathogens. Therefore, ASA was previously reported to be the dominant cause of acute abdominal infections in children.…”
Section: Discussionmentioning
confidence: 99%